Cardiac macrophage subsets differentially regulate lymphatic network remodeling during pressure overload - Mathilde Bizou (Nature Portfolio, 2021)
Abstract The lymphatic network of mammalian heart is an important regulator of interstitial fluid compartment and immune cell trafficking. We observed a remodeling of the cardiac lymphatic vessels and a reduced lymphatic efficiency during heart hypertrophy and failure induced by transverse aortic constriction. The lymphatic endothelial cell number of the failing hearts was positively correlated with cardiac function and with a subset of cardiac macrophages. This macrophage population distinguished by LYVE-1 (Lymphatic vessel endothelial hyaluronic acid receptor-1) and by resident macrophage gene expression signature, appeared not replenished by CCR2 mediated monocyte infiltration during pressure overload. Isolation of macrophage subpopulations showed that the LYVE-1 positive subset sustained in vitro and in vivo lymphangiogenesis through the expression of pro-lymphangiogenic factors. In contrast, the LYVE-1 negative macrophage subset strongly expressed MMP12 and decreased the endothelial LYVE-1 receptors in lymphatic endothelial cells, a feature of cardiac lymphatic remodeling in failing hearts. The treatment of mice with a CCR2 antagonist during pressure overload modified the proportion of macrophage subsets within the pathological heart and preserved lymphatic network from remodeling. This study reports unknown and differential functions of macrophage subpopulations in the regulation of cardiac lymphatic during pathological hypertrophy and may constitute a key mechanism underlying the progression of heart failure.